2004
DOI: 10.1016/j.orggeochem.2004.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of peptide moieties in three Spanish sulfur-rich Tertiary kerogens

Abstract: Thermochemolysis with tetramethylammonium hydroxide (TMAH) and solid-state 15 N NMR were utilized for the characterization of refractory organic nitrogen in Tertiary Spanish kerogens. The samples included sulfur-rich oil shales from the Ribesalbes (Serravallian), Libros (Tortonian) and Cerdanya (Tortonian) basins. Analysis using solid state 15 N NMR showed that part of the refractory nitrogen in the kerogens corresponds to amide groups. Moreover, the release of amino acid derivatives after pyrolysis in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Phenylalanine and tyrosine contribution is revealed by their deamination products [11,12,16,17,19,30], aspartic acid by its cyclisation product, 2,5-pyrrolidine dione [11,12] and lysine by the N-methyl, 2-aminohex-5-enoic acid methyl ester [12,16]. 5-Oxoproline, methyl ester is often detected in these pyrolysates and interpreted as originating from glutamic acid [12] or from aspartic acid [11,[13][14][15][16]30]. Similarly, 2,5-pyrrolidinedione is commonly identified in TMAH pyrolysates [11,12,18,19,30] and is sometimes assigned to aspartic acid [11,12].…”
Section: Implications For Studies Of Natural Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…Phenylalanine and tyrosine contribution is revealed by their deamination products [11,12,16,17,19,30], aspartic acid by its cyclisation product, 2,5-pyrrolidine dione [11,12] and lysine by the N-methyl, 2-aminohex-5-enoic acid methyl ester [12,16]. 5-Oxoproline, methyl ester is often detected in these pyrolysates and interpreted as originating from glutamic acid [12] or from aspartic acid [11,[13][14][15][16]30]. Similarly, 2,5-pyrrolidinedione is commonly identified in TMAH pyrolysates [11,12,18,19,30] and is sometimes assigned to aspartic acid [11,12].…”
Section: Implications For Studies Of Natural Samplesmentioning
confidence: 99%
“…The occurrence of indole derivatives is also generally considered as indicative of tryptophan [18,19,29]. Additional peaks, although not identified but characterized by a base peak at m/z 116 were attributed to amino acid derivatives [13][14][15].…”
Section: Implications For Studies Of Natural Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…In such an environment we are likely to find high amounts of ammonia/ amines from the mineralization by microorganisms. There is evidence for the presence of amino acids during the formation of sulfur rich kerogen (Riboulleau et al, 2002;del Rio et al, 2004). These authors reported on the preservation of amino acids (mainly glycine) by the sulfur crosslinked matrix of the kerogen.…”
Section: Enhancement In the Polymerization Rate In Depositional Envirmentioning
confidence: 99%